2019
DOI: 10.1111/jph.12856
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis reveals changes in transcriptomes of sugarcane upon infection by Leifsoniaxyli subsp. xyli

Abstract: Ratoon stunting disease (RSD) caused by bacterium Leifsoniaxyli subsp. xyli (Lxx) is a devastating disease of sugarcane over a large part of the world. Genetic improvement for RSD‐resistant varieties is considered the most effective method to control the disease. However, genetic improvement of sugarcane is hindered by the limited information about the molecular mechanisms underlying Lxx pathogenicity and defence responses in sugarcane. In this study, genome‐wide gene expression profiling was used to compare R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In this study, we proposed that ABA signal transduction pathway may play negative or unimportant role on sugarcane resistance to X. albilineans, as validated by the upregulation of PYL (a receptor complex of ABA) in susceptible cultivar ROC20 but no significant change in the transcripts expression of SNRK2 gene in two cultivars. Recently, a similar result presented by Fu et al (2019) showed that the susceptible genotype accumulated higher level ABA receptor PYR/PYL than the resistant genotype at 24 hpi under Lxx infection [24]. An additional case by Su et al (2016) demonstrated that a protein phosphates 2C (PP2C, a negative regulator) that was responsible for ABA signaling was upregulated in smut-susceptible cultivar ROC22, but remained unchanged in smut-resistance cultivar Yacheng05-179, suggesting the ABA pathway was not involved or at least unimportant in the defense response of sugarcane to S. scitamineum [51].…”
Section: Plant Hormone Signal Transduction Pathways Involved In the Rsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we proposed that ABA signal transduction pathway may play negative or unimportant role on sugarcane resistance to X. albilineans, as validated by the upregulation of PYL (a receptor complex of ABA) in susceptible cultivar ROC20 but no significant change in the transcripts expression of SNRK2 gene in two cultivars. Recently, a similar result presented by Fu et al (2019) showed that the susceptible genotype accumulated higher level ABA receptor PYR/PYL than the resistant genotype at 24 hpi under Lxx infection [24]. An additional case by Su et al (2016) demonstrated that a protein phosphates 2C (PP2C, a negative regulator) that was responsible for ABA signaling was upregulated in smut-susceptible cultivar ROC22, but remained unchanged in smut-resistance cultivar Yacheng05-179, suggesting the ABA pathway was not involved or at least unimportant in the defense response of sugarcane to S. scitamineum [51].…”
Section: Plant Hormone Signal Transduction Pathways Involved In the Rsupporting
confidence: 76%
“…avenae causing red stripe disease [22] and Leifsonia xyli subsp. xyli (Lxx) causing ratoon stunting disease [23,24]. These findings showed that many common genes and the pathways they are involved with constitute important clues for further investigation of sugarcane-pathogen interactions.…”
Section: Introductionmentioning
confidence: 90%
“…Several transcriptomic studies have revealed the functions of endophytic bacteria during symbiosis between plants and phytopathogens ( Ling et al., 2018 ; Fu et al., 2019 ; Zhu et al., 2021 ). These promising results suggest that dual RNA-seq analyses could be used to understand the physiological and molecular mechanism interactions between novel PGPB and crops.…”
Section: Introductionmentioning
confidence: 99%